Optimization of a CRISPR-Cas9 in vitro protocol for targeting the SIX9 gene of Fusarium oxysporum f.sp. cubense race 1 associated with banana Fusarium wilt - Villao, Liliana; Vargas, Jeffrey; Diez, Nardy; Magdama, Freddy; Santos-Ordóñez, Efrén (Frontiers in Plant Science, 2025)
IntroductionFusarium wilt of bananas (Musa spp.), a threat to sustainable banana production worldwide, necessitates immediate action to control the disease. The current strategies are centered on preventing its spread or developing resistant varieties. However, very little is known about the genetic machinery used by the fungus to infect and kill banana plants. Therefore, research should the focused also in understanding the plant-pathogen molecular interaction by targeting virulent genes for knock-out in Fusarium. This study aims to standardize a gene editing protocol using CRISPR Cas9 technology in Fusarium oxysporum f.sp. cubense race 1 (Foc1); specifically, to induce targeted mutations on a particular effector gene, SIX9, of Foc1.MethodsAn in vitro protocol was optimized for the production of the Cas9 protein to target the SIX9 gene testing two gRNAs, by expression and purification of the Cas9, included in plasmids pHis-parallel1 and pMJ922, in E. coli BL21 Rosetta, independently.ResultsResults demonstrated that the produced Cas9 exhibits high enzymatic activity, comparable to the commercial standard. These findings underscore the robustness of the in-house enzyme and highlight its suitability for future research and biotechnological applications.DiscussionThis protocol facilitates the production of recombinant Cas9, enabling its use in various experimental settings and accelerating research in targeted gene editing, an area of significant relevance today. This protocol will support future studies on banana-Fusarium interaction by identifying candidate genes for disease resistance for the plant, or lack of virulence for the pathogen, by establishing the function of SIX effector proteins and evaluating the fungus’s infection capacity through pathogenicity assays.